#### Answer

G. $r=\sqrt {\frac{Gm_{1}m_{2}}{F}}$

#### Work Step by Step

Multiply both sides of the equation by $r^{2}$. This cancels out $r^{2}$ on the right side of the equation.
$r^{2}{\times}F={\frac{Gm_{1}m_{2}}{r^{2}}}{\times}r^{2}$
$r^{2}{\times}F={Gm_{1}m_{2}}$
Divide both sides of the equation by F. This cancels out F out on the left side of the equation.
$\frac{r^{2}{\times}F}{F}=\frac{{Gm_{1}m_{2}}}{F}$
$r^{2}=\frac{{Gm_{1}m_{2}}}{F}$
Take the square root of both sides of the equation. The power on r and the square root cancel one another out.
$\sqrt {r^{2}}=\sqrt {\frac{{Gm_{1}m_{2}}}{F}}$
$r=\sqrt {\frac{{Gm_{1}m_{2}}}{F}}$